Lack of cone mediated retinal function increases susceptibility to form-deprivation myopia in mice. (March 2019) - Chakraborty, Ranjay; Yang, Victoria; Park, Han na; Landis, Erica G.; Dhakal, Susov; Motz, Cara T.; Bergen, Michael A.; Iuvone, P. Michael; Pardue, Machelle T.
Abstract: Retinal photoreceptors are important in visual signaling for normal eye growth in animals. We used Gnat2 cplf3/cplf3 ( Gnat2 −/− ) mice, a genetic mouse model of cone dysfunction to investigate the influence of cone signaling in ocular refractive development and myopia susceptibility in mice. Refractive development under normal visual conditions was measured for Gnat2 −/− and age-matched Gnat2 +/+ mice, every 2 weeks from 4 to 14 weeks of age. Weekly measurements were performed on a separate cohort of mice that underwent monocular form-deprivation (FD) in the right eye from 4 weeks of age using head-mounted diffusers. Refraction, corneal curvature, and ocular biometrics were obtained using photorefraction, keratometry and optical coherence tomography, respectively. Retinas from FD mice were harvested, and analyzed for dopamine (DA) and 3, 4-dihydroxyphenylacetate (DOPAC) using high-performance liquid chromatography. Under normal visual conditions, Gnat2 +/+ and Gnat2 −/− mice showed similar refractive error, axial length, and corneal radii across development (p > 0.05), indicating no significant effects of the Gnat2 mutation on normal ocular refractive development in mice. Three weeks of FD produced a significantly greater myopic shift in Gnat2 −/− mice compared to Gnat2 +/+ controls (−5.40 ± 1.33 D vs −2.28 ± 0.28 D, p = 0.042). Neither the Gnat2 mutation nor FD altered retinal levels of DA or DOPAC. Our results indicate that cone pathways needed for high acuity vision in primates are not as critical for normal refractive development in mice, and that both rods and cones contribute to visual signalling pathways needed to respond to FD in mammalian eyes.